Synthesis of N-vinylindoles through copper catalyzed cyclization reaction of N-(2-alkynylphenyl)imine1. Issue 25 (7th July 2015) - Wang, Zhi-Qiang; Zhang, Xu; Yu, Lin-Tao; Mao, Wu-Tao; Chen, Chang-Zhong; Xu, Kun
<x xml:space="preserve">Abstract</x> A Cu(ii)-catalyzed cyclization reaction of N-(2-alkynylphenyl)imine to synthesize substituted N-vinylindoles is developed.